Development Of Sensorless Speed Control Based On Back-Emf Zero Crossing For Three-Phase Brushless Dc Motor - Ishak, Izzat Nur Laila (2017)
This research focuses on design development and hardware implementation for a sensorless operation to drive a 16-pole, three-phase Brushless DC Motor. The proposed operation adopted a dsPIC30F3010 digital signal controller developed by Microchip Technology Inc. The digital signal controller has the advantage of low-cost implementation, small and compact size factors and minimum hardware requirements. The development board used in this research is PICDEM MC LV development board produced by Microchip Technology Inc. The development board provides a cost-effective method in developing and evaluating a sensorless motor application. By using this board together with the digital signal controller, a sensorless motor application using Back-EMF zero-crossing technique is implemented and used to derive the commutation sequence. The no-load experimental results shows that at 50% duty cycle, the motor speed is about 2393 rpm with terminal voltage 10.08V, and at 80% duty cycle, the maximum motor speed is about 4110 rpm with terminal voltage 11.98V. The speed controller produces motor speed that is proportional to terminal voltage supply. Therefore, it confirms the theoretical principle of BLDC motor operation.